Antibacterial Activity of Cymbopogon citratus Extract Against Post-Endodontic Bacteria: A Disc Diffusion Study - Rina Permatasari; Nasywa Khabiza Zauhayr; Syarla Feonisa Alzena (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Root canal treatment failure is frequently associated with persistent microbial infection, particularly by Enterococcus faecalis and Staphylococcus aureus. Sodium hypochlorite remains the gold standard irrigant; however, its cytotoxicity has encouraged the exploration of herbal alternatives. Cymbopogon citratus contains bioactive compounds with potential antibacterial properties. Material and Methods: This laboratory experimental study evaluated the antibacterial activity of Cymbopogon citratus extract at concentrations of 10%, 20%, and 30% against E. faecalis ATCC 29212 and S. aureus ATCC 29213 using the disc diffusion method. Sodium hypochlorite 2.5% was used as the positive control and 96% ethanol as the negative control. Data were analyzed using one-way ANOVA followed by Bonferroni post hoc test. Results and Discussion: The highest inhibition zone for E. faecalis was observed at 20% concentration (1.63 ± 0.48 mm), while for S. aureus, the highest value was found at 10% concentration (2.06 ± 1.15 mm). No statistically significant differences were found among extract concentrations (p>0.05), whereas sodium hypochlorite demonstrated significantly higher antibacterial activity (p<0.001). Conclusion: Cymbopogon citratus extract demonstrated weak antibacterial activity and was not comparable to sodium hypochlorite. Its potential as an alternative root canal irrigant requires further optimization and validation.